2018
DOI: 10.1002/fsn3.725
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. and Campylobacter spp. in poultry feces and carcasses in Ouagadougou, Burkina Faso

Abstract: The importance of Salmonella and Campylobacter as foodborne pathogens is well recognized worldwide. Poultry and poultry products are commonly considered as the major vehicles of Salmonella and Campylobacter infection in humans. The aim of this study was to investigate the hygienic status of poultry facilities and determine the prevalence of Salmonella and Campylobacter in slaughtered poultry feces and carcasses in four different markets in Ouagadougou, capital city of Burkina Faso. A total of 103 poultry feces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
1
21
2
1
Order By: Relevance
“…In this case, the data are more difficult to relate to the flock infection status. Cross-contamination between slaughter batches at the abattoir occurs commonly, but in situations where there is a low flock prevalence of either Salmonella or Campylobacter carcass contamination is most likely to originate from the flock itself rather than the slaughter process (Kagambega et al, 2018). Several studies report associations between the contamination of farm samples and processing plant samples for Salmonella and Campylobacter (Arsenault et al, 2007;Hue et al, 2011;Franz et al, 2012;Berghaus et al, 2013).…”
Section: Data From Eea Countriesmentioning
confidence: 99%
“…In this case, the data are more difficult to relate to the flock infection status. Cross-contamination between slaughter batches at the abattoir occurs commonly, but in situations where there is a low flock prevalence of either Salmonella or Campylobacter carcass contamination is most likely to originate from the flock itself rather than the slaughter process (Kagambega et al, 2018). Several studies report associations between the contamination of farm samples and processing plant samples for Salmonella and Campylobacter (Arsenault et al, 2007;Hue et al, 2011;Franz et al, 2012;Berghaus et al, 2013).…”
Section: Data From Eea Countriesmentioning
confidence: 99%
“…In Ouagadougou, Burkina Faso, Campylobacter was detected in 50% of 20 poultry carcasses sourced from retail markets [70]. The carcasses were sold on tables in ambient temperatures without protection from dust or flies, the vendors did not wear gloves or aprons, and the retail environment was infested with lizards, rodents, and avian species.…”
Section: Prevalence Of Campylobacter In Foods Of Animal Originmentioning
confidence: 99%
“…The carcasses were sold on tables in ambient temperatures without protection from dust or flies, the vendors did not wear gloves or aprons, and the retail environment was infested with lizards, rodents, and avian species. Kagambèga, Thibodeau, Trinetta, Soro, Sama, Bako, Bouda, Wereme N’Diaye, Fravalo and Barro [70] suggested that, although poultry is widely consumed in Burkina Faso, patients with diarrhoea are not routinely sampled for Campylobacter . However, in neighbouring Ghana, a lower isolation rate of 21.9% was detected in 132 poultry carcasses randomly selected from the Kejetia poultry slaughter unit in Kumasi [71].…”
Section: Prevalence Of Campylobacter In Foods Of Animal Originmentioning
confidence: 99%
“…In the present study, Salmonella was detected in 24.69% of all the poultry intestines samples analyzed with 20.45% in slaughtered chicken intestines and 22.26% in slaughtered guinea fowl intestines. In contrast, a high prevalence of Salmonella in slaughtered poultry intestines were detected in the studies conducted by Kagambega et al (2013) (55%) [18] and 2018 (52.42%) [9] in Burkina Faso; Andoh et al (2016) in Ghana (47%) [19] and Bai et al (2015) in China (45.2%) [20]. This difference could be explained by sampling conditions, isolation method and period of sampling.…”
Section: Discussionmentioning
confidence: 83%
“…Salmonella has been reported to be the second most pathogen affecting foodborne illnesses in Burkina Faso [6,7]. Poultry is an important reservoir of many zoonotically pathogens, mainly Salmonella and Campylobacter [8,9]. Poultry meat can acquire Salmonella from intestinal contents, faecal material or from cross-contamination during slaughtering processes [10].…”
Section: Introductionmentioning
confidence: 99%